Preclinical Evaluation of Oncolytic Δγ134.5 Herpes Simplex Virus Expressing Interleukin-12 for Therapy of Breast Cancer Brain Metastases - Cody, James J.; Scaturro, Pietro; Cantor, Alan B.; Yancey Gillespie, G.; Parker, Jacqueline N.; Markert, James M. (International Journal of Breast Cancer, 2012)
The metastasis of breast cancer to the brain and central nervous system (CNS) is a problem of increasing importance. As improving treatments continue to extend patient survival, the incidence of CNS metastases from breast cancer is on the rise. New treatments are needed, as current treatments are limited by deleterious side effects and are generally palliative. We have previously described an oncolytic herpes simplex virus (HSV), designated M002, which lacks both copies of the γ134.5 neurovirulence gene and carries a murine interleukin 12 (IL-12) expression cassette, and have validated its antitumor efficacy in a variety of preclinical models of primary brain tumors. However, M002 has not been yet evaluated for use against metastatic brain tumors. Here, we demonstrate the following: both human breast cancer and murine mammary carcinoma cells support viral replication and IL-12 expression from M002; M002 replicates in and destroys breast cancer cells from a variety of histological subtypes, including “triple-negative” and HER2 overexpressing; M002 improves survival in an immunocompetent model more effectively than does a non-cytokine control virus. Thus, we conclude from this proof-of-principle study that a γ134.5-deleted IL-12 expressing oncolytic HSV may be a potential new therapy for breast cancer brain metastases.